2017
DOI: 10.1007/s00429-017-1370-x
|View full text |Cite
|
Sign up to set email alerts
|

Microglia in the primate macula: specializations in microglial distribution and morphology with retinal position and with aging

Abstract: Microglia, the principal resident immune cell in the retina, play constitutive roles in immune surveillance and synapse maintenance, and are also associated with retinal disease, including those occurring in the macula. Perspectives on retinal microglia function have derived largely from rodent models and how these relate to the macula-bearing primate retina is unclear. In this study, we examined microglial distribution and cellular morphology in the adult rhesus macaque retina, and performed comparative chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 48 publications
4
27
0
Order By: Relevance
“…The pooled average of DL density at 17% is similar to that reported for perifovea 25 previously and comparable with the peripheral retina at 16.12%. 24 We identified an increase in vessel density with increasing eccentricity between the foveola and parafoveal region of 14% to 20%, which corresponds very well with the eccentric increase in rods 1 and microglia 34 density, suggesting a dependency relationship of the rod photoreceptors on the DL. The density of macular DL also was found to be very stable across the age groups.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The pooled average of DL density at 17% is similar to that reported for perifovea 25 previously and comparable with the peripheral retina at 16.12%. 24 We identified an increase in vessel density with increasing eccentricity between the foveola and parafoveal region of 14% to 20%, which corresponds very well with the eccentric increase in rods 1 and microglia 34 density, suggesting a dependency relationship of the rod photoreceptors on the DL. The density of macular DL also was found to be very stable across the age groups.…”
Section: Discussionsupporting
confidence: 67%
“…A recent study on monkey eyes identified an increase in microglia density with age in the macular region. 34 As the microglia are known to have a tiled distribution in the inner retina with processes concentrated in the inner plexiform layer and OPL, their increased presence in aged eyes could have contributed to the increased metabolic demands of the inner retina, potentially inducing increased vascular growth and inflammatory responses. More detailed study on the age-related change in microglia and metabolic demand of the human inner macular will be needed to clarify this point.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia are primarily distributed in the plexiform layers of the foveal walls, whereas the foveola is largely microglia‐free (Singaravelu et al. ). There are two different populations of Müller cells in the fovea: specialized Müller cells that form the Müller cell cone in the foveola (Yamada ; Gass ; Syrbe et al.…”
Section: Introductionmentioning
confidence: 99%
“…The only type of macroglia in the fovea is Müller glia; astrocytes are located in the parafovea (Figure a) (Bringmann et al, ; Distler & Dreher, ). Microglia are distributed in the NFL/GCL and plexiform layers of the foveal walls whereas the foveola is largely microglia‐free (Singaravelu, Zhao, Fariss, Nork, & Wong, ). Because microglia are pivotal for the maintenance of the photoreceptor cell synapses in the OPL (Wang et al, ), the absence of microglia in the foveola corresponds with the absence of synapses.…”
Section: Müller Cells Of the Foveamentioning
confidence: 99%